Morphine and codeine concentrations in human urine following controlled poppy seeds administration of known opiate content. - Smith, Michael L; Nichols, Daniel C; Underwood, Paula; Fuller, Zachary; Moser, Matthew A; LoDico, Charles; Gorelick, David A; Newmeyer, Matthew N; Concheiro, Marta; Huestis, Marilyn A (Forensic Science International, 2014)
Opiates are an important component for drug testing due to their high abuse potential. Proper urine opiate interpretation includes ruling out poppy seed ingestion; however, detailed elimination studies after controlled poppy seed administration with known morphine and codeine doses are not available. Therefore, we investigated urine opiate pharmacokinetics after controlled oral administration of uncooked poppy seeds with known morphine and codeine content. Participants were administered two 45 g oral poppy seed doses 8 h apart, each containing 15.7 mg morphine and 3mg codeine. Urine was collected ad libitum up to 32 h after the first dose. Specimens were analyzed with the Roche Opiates II immunoassay at 2000 and 300 μg/L cutoffs, and the ThermoFisher CEDIA(®) heroin metabolite (6-acetylmorphine, 6-AM) and Lin-Zhi 6-AM immunoassays with 10 μg/L cutoffs to determine if poppy seed ingestion could produce positive results in these heroin marker assays. In addition, all specimens were quantified for morphine and codeine by GC/MS. Participants (N=22) provided 391 urine specimens over 32 h following dosing; 26.6% and 83.4% were positive for morphine at 2000 and 300 μg/L GC/MS cutoffs, respectively. For the 19 subjects who completed the study, morphine concentrations ranged from <300 to 7522 μg/L with a median peak concentration of 5239 μg/L. The median first morphine-positive urine sample at 2000 μg/L cutoff concentration occurred at 6.6 h (1.2-12.1), with the last positive from 2.6 to 18 h after the second dose. No specimens were positive for codeine at a cutoff concentration of 2000 μg/L, but 20.2% exceeded 300 μg/L, with peak concentrations of 658 μg/L (284-1540). The Roche Opiates II immunoassay had efficiencies greater than 96% for the 2000 and 300 μg/L cutoffs. The CEDIA 6-AM immunoassay had a specificity of 91%, while the Lin-Zhi assay had no false positive results. These data provide valuable information for interpreting urine opiate results.